2001
DOI: 10.1177/089686080102100612
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Degradation Products in Peritoneal Dialysis Fluids May Have Both Local and Systemic Effects: A Study of Residual Fluid and Mesothelial Cells

Abstract: Objective When peritoneal dialysis (PD) fluids are heat sterilized, glucose is degraded to carbonyl compounds. These compounds are known to interfere with many cellular functions and to promote the formation of advanced glycation end-products. However, little is known about what actually happens with glucose degradation products (GDPs) after infusion into the peritoneal cavity. The aim of the present study was to investigate possible targets for GDPs in the peritoneal cavity. Design In vitro reactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Several of these GDPs, such as 3-deoxyglucosone (3-DG), 3,4-dideoxyglucosone-3-ene (3,4-DGE), glyoxal, methylglyoxal, 5-hydroxymethylfurfural (5-HMF), 2-furaldehyde (2-FA), formaldehyde and acetaldehyde, have previously been identified in peritoneal dialysis and infusion fluids 3 , 8 , 9 . It has already been demonstrated that GPDs are highly reactive precursors of Advanced Glycation End products (AGEs) 6 , 10 , 11 in proteins. AGEs result from a chemical reaction when reduced carbohydrates (such as glucose) react with amino acids or nucleotides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these GDPs, such as 3-deoxyglucosone (3-DG), 3,4-dideoxyglucosone-3-ene (3,4-DGE), glyoxal, methylglyoxal, 5-hydroxymethylfurfural (5-HMF), 2-furaldehyde (2-FA), formaldehyde and acetaldehyde, have previously been identified in peritoneal dialysis and infusion fluids 3 , 8 , 9 . It has already been demonstrated that GPDs are highly reactive precursors of Advanced Glycation End products (AGEs) 6 , 10 , 11 in proteins. AGEs result from a chemical reaction when reduced carbohydrates (such as glucose) react with amino acids or nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…Although precise thresholds of toxicity are not yet known for GDPs and AGEs administered to chronically-ill patients, it has been shown that high levels of GDPs and AGEs have an impact on cell homeostasis 1 , 9 , 17 19 , are involved in oxidative stress 20 , 21 , are associated with cellular inhibition 22 , induce apoptosis in human leukocytes and renal epithelial cells 1 , 18 , 23 , cause degradation of mesothelial cells and peritoneal membrane characteristics 6 , 23 – 25 , have an impact on the cardiovascular system 21 , 26 , 27 , are associated with an increase in cardiovascular morbidity 28 and a decline in renal function 29 or cause kidney damage 1 , 8 , 30 . Other studies have shown that the accumulation of AGEs in patients suffering from diabetes mellitus can lead to microvascular complications 6 such as diabetic retinopathy 20 or diabetic vascular complications 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GDPs and heat sterilized PD fluids showed a cytotoxic activity against peritoneal mesothelium cells in vitro (Witowski et al, 2000). There is also evidence that GDPs in PD fluids exert their harmful effects not only locally in the peritoneum, but that they enter the body across the peritoneal membrane (Tauer et al, 2005;Linden et al, 2001;Zeier et al, 2003). As a result, they may increase systemic carbonyl stress leading to systemic AGE formation, decline in renal function (Lee et al, 2005;Williams et al, 2004) and overall lowered patient survival (Williams et al, 2004;Lee et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The glucose content of the dialysate has been incriminated in the alteration of the peritoneal membrane. Heat sterilization of PD fluids degrades glucose into a variety of carbonyl compounds such as methylglyoxal, glyoxal and 3‐deoxyglucosone [4,5], all of which are cytotoxic and mitogenic [6,7]. These products also lead to advanced glycation of proteins [8,9], associated with age‐related disorders and with diabetic or uremic complications [10–13].…”
Section: Introductionmentioning
confidence: 99%
“…The present paper assesses the possible role of VEGF in the modification of peritoneal membrane characteristics. More specifically, we examine the effect of methylglyoxal, a major glucose degradation product (GDP) [4,5], on the production of VEGF, both in vitro in cultured peritoneal mesothelial and endothelial cells and in vivo in peritoneal tissues of rats. We also examine by immunohistochemistry the distributions of VEGF and GDP‐modified proteins in peritoneal tissues obtained from long‐term PD patients.…”
Section: Introductionmentioning
confidence: 99%